2013
DOI: 10.1111/ene.12237
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid biomarkers of neurodegeneration in patients with juvenile and classic myotonic dystrophy type 1

Abstract: The CSF level of Aβ42 was decreased in patients with jDM1, whilst the Aβ42/P-tau ratio was decreased in aDM1 patients. Positive correlations between Aβ42 , T-tau and P-tau were observed in both forms of disease. Further studies with larger cohorts of DM1 patients are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 31 publications
4
19
2
Order By: Relevance
“…In our study, DM1 patients also showed a severe involvement of the dorsolateral prefrontal cortex, cingulum, medial and lateral parietal regions, occipital and temporal lobes, that has been associated with cognitive deficits and personality changes in many neurological and psychiatric diseases. Similar symptoms, such as mild depression and anxiety as well as deficits of visuospatial abilities, executive functions, reasoning and naming, have been frequently reported in DM1 patients [6], [25], [39], [40], including those of our study.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In our study, DM1 patients also showed a severe involvement of the dorsolateral prefrontal cortex, cingulum, medial and lateral parietal regions, occipital and temporal lobes, that has been associated with cognitive deficits and personality changes in many neurological and psychiatric diseases. Similar symptoms, such as mild depression and anxiety as well as deficits of visuospatial abilities, executive functions, reasoning and naming, have been frequently reported in DM1 patients [6], [25], [39], [40], including those of our study.…”
Section: Discussionsupporting
confidence: 89%
“…Some authors suggested that symptoms of juvenile DM1 begin after 1 month of life and before the age of 10 years [1], [51], others indicated that juvenile DM1 is defined by onset before 16 years of age [52]. In the present and in two previous studies [25], [53], we defined juvenile DM1 cases those subjects with symptom onset before the age of 20 years, since such a cut-off is often used for dividing juvenile and adult forms in different neurological disorders, for instance in parkinsonism. In 2000, the International Myotonic Dystrophy Consortium [54] suggested that the age at onset and disease severity of DM1 significantly correlate with the number of CGT repeats.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Decreased Aβ 1-42 levels in the CSF have also been observed in various tauopathies and other diseases, such as Creutzfeld-Jacob disease and Multiple System Atrophy (Van Everbroeck et al, 1999; Otto et al, 2000; Sjogren et al, 2002; Noguchi et al, 2005). Interestingly, the analysis of CSF in DM patients also revealed a significant decrease in Aβ 1-42 compared with matched controls (Winblad et al, 2008; Peric et al, 2013a). While a decrease in the Aβ 1-42 level in the CSF of AD patients is associated with the presence of the cerebral aggregation of this peptide, this is not the case for other tauopathies, particularly DM (Kiuchi et al, 1991; Figure 1).…”
Section: Common Features Of Dm and Other Tauopathiesmentioning
confidence: 98%
“…Biomarkers of neurodegeneration such as tau and amyloid ß42 protein (Aß42) were investigated in juvenile and adult DM1 patients. A significant decrease of CSF levels of Aß42 was reported as well as increase of the levels of total tau protein (Winblad et al, 2008; Peric et al, 2014a). No correlation between the levels of these CSF biomarkers and neuropsychological impairment were evident.…”
Section: Dm Biomarkers For Cns Abnormalitiesmentioning
confidence: 99%